Implementasi Sistem Manajemen Keselamatan Dan Kesehatan Kerja Rumah Sakit Di RSUD Jatisari - Putri Dwi Rahayu; Sungkono; Dedi Mulyadi (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
Hospitals are health facility services that face various problems and various risks related to work and work accidents according to the type of work. The implementation of the Occupational Safety and Health Management System (SMK3) at Jatisari Regional General Hospital aims to create a healthy, safe, secure, comfortable, efficient and productive work environment for hospital human resources, both patients, patient assistants, and visitors as well as knowing the Implementation of the Occupational Safety and Health Management System at Jatisari Regional General Hospital. This research uses a descriptive method with a qualitative approach. Data collection techniques were carried out through in-depth interviews. The results showed that the implementation of SMK3 in Jatisari Regional General Hospital has generally been carried out with several stages, such as the establishment of K3RS policy, K3RS planning, K3RS implementation, K3RS monitoring and evaluation, and review and improvement of SMK3 performance.